Implementation of the Al-Miftah Method in Nahwu Instruction at MTs Darul Muhajirin Putra - Muhamad Hasyim (Formad English Foundation NTB-Jakarta, 2025)
This study is motivated by the limited research on the implementation of the Al-Miftah method in formal madrasah settings, despite its significant impact on improving students’ Arabic grammar proficiency. The study aims to examine how the Al-Miftah modules are applied in classroom instruction, analyze students’ comprehension and motivational responses, and identify learning outcomes resulting from the method’s integration. This research adopts a qualitative case study design, with 25 participants consisting of Arabic language teachers and grade VIII students selected through purposive sampling. Data were collected using semi-structured interviews, classroom observations, and document analysis, and analyzed through thematic and qualitative content analysis. The findings reveal that the Al-Miftah method enhances students’ understanding of core nahwu principles by providing structured, concise, and visually supported explanations. Students demonstrated improved recognition of grammatical elements such as isim, fi‘il, and harf, accompanied by increased engagement during learning activities. The results also show that the method contributes to measurable improvements in language proficiency across learning cycles, aligning with grammar acquisition theories emphasizing systematic scaffolding and multimodal reinforcement. The study concludes that the Al-Miftah method plays a critical role in strengthening grammar instruction within Islamic secondary education, particularly in contexts where students possess diverse linguistic readiness. The implications encompass theoretical contributions to Arabic grammar pedagogy and practical recommendations for curriculum developers and educators to adopt structured, visually enhanced learning modules. Additionally, this study identifies future research opportunities, including longitudinal analyses and expanded multi-institutional investigations to validate the method’s long-term effectiveness.